2011
DOI: 10.1007/s11661-011-0728-6
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Cu-Al-Ni Shape Memory Alloy Strips Prepared from Prealloyed Powder by Hot Densification Rolling of Powder Preforms

Abstract: The present work deals with the preparation of near-full density Cu-Al-Ni shape memory alloy (SMA) strips from argon-atomized prealloyed powder via a powder metallurgy (PM) route comprising cold die compaction to prepare powder preforms, sintering, and hot densification rolling of unsheathed sintered powder preforms under protective atmosphere at 1273 K (1000°C). It has been shown that argon-atomized spherical Cu-Al-Ni SMA powder consisted of very fine equiaxed grains and no appreciable grain growth occurred d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…This diffractogram shows many peaks suggesting a multi-phase alloy. In this diffractogram, there are the peaks of the Al, the peaks of CuNi [14,44], the peaks of NiAl [45,46] and those of the austenite phase of the Cu-based SMAs [47,48].…”
Section: Characterization Of the Superelasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…This diffractogram shows many peaks suggesting a multi-phase alloy. In this diffractogram, there are the peaks of the Al, the peaks of CuNi [14,44], the peaks of NiAl [45,46] and those of the austenite phase of the Cu-based SMAs [47,48].…”
Section: Characterization Of the Superelasticitymentioning
confidence: 99%
“…Thus, their disadvantages have restricted the use of these alloys for commercial applications in particular in SE applications. One way to solve these problems is to refine the grain of the CuAlNi SMAs by adding some alloying elements such as Be or by varying the compositions of Ni and Al [12][13][14]. These changes have shown some improvement in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that powder metallurgy (PM)-based processing approach is an effective technique to achieve fine-grained Cu-Al-Ni alloys with high strength and reasonable ductility [23][24][25][26][27][28][29][30]. Most of the PM-based approaches involved either elemental or pre-alloyed powders as starting material followed by their consolidation via different methods to prepare bulk material of different shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have aimed to develop fine-grained Cu-Al-Ni alloys, with a grain size considerably less than 100 μ m, by using various powder metallurgy techniques [ 13 , 14 ]. These kinds of techniques depended on the Cu-Al-Ni alloy powder, which was prepared by either an inert gas atomization process or mechanical alloying of elemental powders in a high-energy ball mill under inert gas atmosphere [ 15 ]. The mechanical alloying (MA) method [ 16 , 17 ] is one of the most desired methods; it is indeed reported to be more affordable and also convenient for manufacturing applications.…”
Section: Introductionmentioning
confidence: 99%